Effectiveness of different types of mental simulation in the weight loss process based on a perseverance study among people with different BMI - Wojciech Styk; Szymon Zmorzyński; Waldemar Klinkosz (Archives of Public Health, 2021)
Abstract Background Most of the world’s population lives in countries in which overweight and obesity kill more people than does underweight. The weight loss process can be supported by mental simulations, which are used to help individuals to effectively strive towards various goals. The aim of this study was to determine the impact of different types of mental simulations on perseverance, resistance to distractors and the ability to inhibit irrelevant thoughts or memories in people with different body mass indexes (BMI). Methods The study included 252 participants. They performed process simulations and outcome simulations, using instructions presented to them during the experiment. Perseverance and resistance to distractors were determined using a computer maze-solving task. Two indicators of perseverance were analysed: number of maze tasks solved and total time spent on solving the test. Mean time spent on a single task was used as a measure of resistance to distractors and the ability to inhibit irrelevant thoughts and memories. Results The results of the analyses showed that the type of mental simulation used had an effect on the indicators of perseverance. Process simulation subjects completed more tasks and spent more time solving the test than outcome simulation subjects. A relationship was found between the subjects’ BMI and the investigated indicators. Individuals who were underweight, overweight or obese scored lower on all three indicators compared to subjects with normal BMI. In people with a BMI above normal, mental simulations increased resistance to distractors and the ability to inhibit thoughts sidetracking them from the task at hand. It is possible that increasing the resistance to distractors is responsible for the effectiveness of mental simulations in the weight loss process. Conclusion Our results can be applied in developing interventions for people who suffer from overweight and obesity. Psychological interventions based on mental simulations can be used to assist individuals in physical activity, leading to an improvement in health, but it has to be underlined that the mechanism of their action may vary from person to person.